Effect of a behavior change and hardware intervention on safe child feces management practices in rural Odisha, India: a cluster-randomized controlled trial - Gloria D. Sclar; Valerie Bauza; Alokananda Bisoyi; Fiona Majorin; Hans-Joachim Mosler; Thomas F. Clasen (BMC, 2024)
Abstract Background Poor child feces management contributes to enteropathogen exposure and, consequently, is associated with diarrheal disease and negative impacts on child growth. Despite high latrine coverage, only 37% of Indian households safely dispose of their child's feces into a latrine or have the child use the latrine, with the lowest rate in the state of Odisha at 12%. We evaluated a behavior change and hardware intervention designed to improve caregiver safe disposal of child feces and child latrine use. Methods We conducted a cluster-randomized controlled trial among 74 villages in rural Odisha, India. Eligible villages previously participated in a water and sanitation infrastructure program. Following a baseline survey, half the villages were assigned to intervention and half to control. Caregivers of children < 5 years old from households with a latrine were eligible to participate. The intervention included five behavior change activities. Hardware was provided at the first activity, based on child age, to aid safe disposal and latrine training (wash basin and bucket with lid for children < 7 months old; latrine training mat platform with removable tray for children 7 to 48 months old). The primary outcome was caregiver reported 'safe disposal' as defined by the WHO/UNICEF Joint Monitoring Programme (JMP) which encompasses two behaviors: caregiver disposal of child's feces into a latrine and child latrine use. Safe disposal was measured four to six months after intervention delivery (endline). Results Endline analysis included 665 intervention caregivers (840 children) and 634 control caregivers (785 children). Prevalence of JMP-defined safe disposal was 1.16 times greater in the intervention arm compared to control (77.7% vs. 65.9%; prevalence ratio [PR] 1.16, 95% CI 1.04-1.29), with higher prevalence of caregiver safe disposal (18.6% vs. 13.6%; PR 1.46, 95% CI 1.12-1.92) but no significant difference in child latrine use (59.0% vs. 52.2%; PR 1.06, 95% CI 0.95-1.18). When restricted to children < 3 years old, JMP-defined safe disposal was 1.42 times greater (67.5% vs. 46.7%; PR 1.42 95% CI 1.21-1.67) with higher prevalence of both caregiver safe disposal (34.6% vs. 25.7%; PR 1.44, 95% CI 1.11-1.86) and child latrine use (32.9% vs. 20.9%; PR 1.41, 95% CI 1.08-1.83). Conclusions The intervention increased JMP-defined safe disposal, with substantial improvements in both caregiver safe disposal and child latrine use among children < 3 years old. While future research is needed to demonstrate sustainability of these effects, our results suggest a potentially scalable intervention for improving child feces disposal and reducing disease. Trial registration This trial was retrospectively registered at ISRCTN15831099 on 18/02/2020, which was approximately two months after the first participant was recruited for the baseline survey on 02/12/2019.